FIRST RECORDS OF FRESHWATER FISHES GARRA GRAVELYl AND G. KEMPl IN MANIPUR - Vishwanath, W; Singh, H Tombi; Singh, O Shashikumar; Sharma, M Gonchandra (Indian Journal of Fisheries, 2011)
Two species of Cyprinid hill stream fishes Garra gravelyi (Annandale) and G. kempi Hora are recorded and described from the streams of Chindwin Drainage, Manipur State.